Diagnostic and therapeutic implications of genetic heterogeneity in myeloid neoplasms uncovered by comprehensive mutational analysis. (2017) - Choi, Sarah M.; Goldenson, Ben; Peterson, Lo Ann; Dinner, Shira; Stein, Brady L.; Behdad, Amir
Abstract: While growing use of comprehensive mutational analysis has led to the discovery of innumerable genetic alterations associated with various myeloid neoplasms, the under-recognized phenomenon of genetic heterogeneity within such neoplasms creates a potential for diagnostic confusion. Here, we describe two cases where expanded mutational testing led to amendment of an initial diagnosis of chronic myelogenous leukemia with subsequent altered treatment of each patient. We demonstrate the power of comprehensive testing in ensuring appropriate classification of genetically heterogeneous neoplasms, and emphasize thoughtful analysis of molecular and genetic data as an essential component of diagnosis and management.